Alcohol‐Related Blackouts, Negative Alcohol‐Related Consequences, and Motivations for Drinking Reported by Newly Matriculating Transgender College Students. (21st March 2017) - Tupler, Larry A.; Zapp, Daniel; DeJong, William; Ali, Maryam; O'Rourke, Sarah; Looney, John; Swartzwelder, H. Scott
Abstract : Background: Many transgender college students struggle with identity formation and other emotional, social, and developmental challenges associated with emerging adulthood. A potential maladaptive coping strategy employed by such students is heavy drinking. Prior literature has suggested greater consumption and negative alcohol‐related consequences (ARCs) in transgender students compared with their cisgender peers, but little is known about their differing experiences with alcohol‐related blackouts (ARBs). We examined the level of alcohol consumption, the frequency of ARBs and other ARCs, and motivations for drinking reported by the largest sample of transgender college students to date. Methods: A Web survey from an alcohol‐prevention program, AlcoholEdu for College ™, assessed student demographics and drinking‐related behaviors, experiences, and motivations of newly matriculating first‐year college students. A self‐reported drinking calendar was used to examine each of the following measures over the previous 14 days: number of drinking days, total number of drinks, and maximum number of drinks on any single day. A 7‐point Likert scale was used to measure ARCs, ARBs, and drinking motivations. Transgender students of both sexes were compared with their cisgender peers. Results: A total of 989 of 422, 906 students (0.2%) identified as transgender. Over a 14‐day period, transgender compared with cisgender students were more likely to consume alcohol over more days, more total drinks, and a greater number of maximum drinks on a single day. Transgender students (36%) were more likely to report an ARB than cisgender students (25%) as well as more negative academic, confrontation‐related, social, and sexual ARCs. Transgender respondents more often cited stress reduction, social anxiety, self‐esteem issues, and the inherent properties of alcohol as motivations for drinking. For nearly all measures, higher values were yielded by male‐to‐female than female‐to‐male transgender students. Conclusions: Transgender compared with cisgender first‐year students engage in higher‐risk drinking patterns and experience more ARBs and other negative ARCs. Broad institutional efforts are required to address the unique circumstances of transgender men and women and to reduce negative ARCs in college students, regardless of their sex or gender identity. Abstract : Transgender college students may be at an increased risk of hazardous drinking due to heteronormative societal pressures. Using a Web survey from an alcohol‐prevention program, we established that transgender compared with cisgender first‐year students engaged in higher‐risk drinking patterns and experienced more alcohol‐related blackouts and other negative alcohol‐related consequences. Transgender respondents more often cited stress reduction, social anxiety, self‐esteem issues, and the inherent properties of alcohol as motivations for drinking. Presentations were more severe for male‐to‐female than female‐to‐male transgender students.